Evaluation of in vivo bond strength and skin irritation test for new skin adhesive - Paweena Kongkon; Wiwat Pichayakorn; Sasiwimol Sanohkan (Elsevier, 2023)
Objectives: This study developed a new skin-deproteinized natural rubber latex (DNRL) silicone adhesive for adhering to silicone prostheses and compared the properties with a commercial Daro-Hydrobond adhesive. Materials and methods: The new DNRL skin adhesive formulation was made from non-vulcanized natural rubber-based adhesives consisting of DNRL, 20% polyvinyl alcohol, cumarone resin, 2% methylcellulose, and Wingstay L. The peel bond strength of the adhesives was tested using a 90-degree peel test. Biocompatibility was accessed using in vitro keratinocyte cell viability. Animals (rabbits) and humans were tested for skin irritation tests. Results were analyzed using SPSS Version 24 and compared between the two adhesives. Results: The peel bond strength of the new DNRL skin adhesive was 103.61 ± 23.18 N/m whereas that of the Daro-hydrobond adhesive was 131.52 ± 21.72 N/m. There was no significant difference (p>0.05) between the peel bond strengths of the two test adhesives. Cell proliferation under the DNRL skin adhesive-soaked medium showed higher cell viability than the positive control (p<0.05). The DNRL skin adhesive produced moderate erythema and edema on rabbit skins, however, the skin lesions recovered within 14 days. Two volunteers showed mild irritation at the first hour of the contact which was reduced within an hour without any therapy. The patient satisfaction with the DNRL skin adhesive ranged from slightly satisfied to completely satisfied. Conclusion: The new DNRL skin adhesive showed comparable peel bond strength and patient satisfaction to those of commercial adhesives. The adhesive was biocompatible and can be used carefully.